2011
DOI: 10.1007/s13277-011-0285-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic value of various preoperative inflammation-based factors in patients with stage III gastric cancer

Abstract: The aim of present study was to examine whether the C-reactive protein (CRP)-based systemic inflammatory response such as the Glasgow Prognostic Score (GPS; a combination of CRP and albumin) offers prognostic value that is superior to the circulating white cellular components as neutrophil/lymphocyte ratio (NLR) or platelet/lymphocyte ratio (PLR) in patients undergoing resection for stage III gastric cancer. The medical records of 324 patients with stage III gastric adenocarcinoma were reviewed. Potential prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 36 publications
8
114
3
Order By: Relevance
“…Whereas, studies from Deshen et al suggested that PLR was not an independent prognostic factor in gastric cancer patients, which we also confirmed in the present study [19]. However, it might be worthy to investigate larger-scale study to validate whether PLR was an independent index.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Whereas, studies from Deshen et al suggested that PLR was not an independent prognostic factor in gastric cancer patients, which we also confirmed in the present study [19]. However, it might be worthy to investigate larger-scale study to validate whether PLR was an independent index.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have proved that NLR is an independent predictor in gastric tumor [18]. However, it is still controversial, Deshen et al demonstrated that NLR was not correlated with OS and EFS in post-operated gastric cancer patients [19]. In our retrospective study, we also demonstrated that NLR was not an independent predictor in DLBCLs.…”
Section: Discussioncontrasting
confidence: 45%
“…Interestingly, some recent studies suggested that Glasgow prognostic score (GPS) was an independent prognostic marker for gastric cancer patients (Hwang et al, 2011;Wang et al, 2012;Jeong et al, 2012). GPS is a combination of serum CRP and albumin concentrations (Forrest et al, 2003), which appears to reflect the systemic inflammatory response as well as nutritional status (Kao et al, 2010;Proctor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although GPS has frequently been associated with the prognosis of solid tumours, such as lung (22,23), liver (27,28), kidney (26), ovarian (24), colorectal (25), gastric (41,42) and pancreatic cancer (43), the association has yet to be fully elucidated. One component of the GPS score, CRP, is an acute phase protein synthesized by hepatocytes in response to inflammation, infection, tissue damage and cancer, reflecting systemic inflammation (44).…”
Section: Discussionmentioning
confidence: 99%